Russia-Ukraine Confrontation: How Does It Affect Market Reaction and Stock Performance of the Mining Sub-Sector? - Alghifari, Mohammad Fauzan; Apriwandi, Apriwandi; Fadila, Egita Nur (E-Jurnal Akuntansi; Vol 34 No 11 (2024)DO - 10.24843/EJA.2024.v34.i11.p08, 2024)
This  research  aims  to  empirically  demonstrate  the  divergence  of  capital  market responses  measured  by  abnormal  returns,  trading  volume,  volatility  of  security returns,  and  stock  performance  measured  by returns  in  the  mining  subsector listed  on  the  IDX  due  to  the  Russia-Ukraine  war.  This  research  is  vital  because geopolitical  conflicts  such  as  the  Russia-Ukraine  War  affect  financial  markets, especially  commodity-dependent  sectors,  thus  providing  insights for  investors and policymakers in the face of uncertainty. Using an event study method for 10 days  pre-and  post-war,  this  research  used  29  companies  with  paired  sample  t-tests in the hypothesis testing. This study is the first to combine the four variables AR, TVA, SRV, and R to analyze the impact of the Russia-Ukraine conflict, thus becoming a novelty in this  research. This study  revealed a significant change  in TVA. At the same time, no considerable divergence was found in AR, SRV, and R in mining subsector companies listed on the IDX, both before and after the Russia-Ukraine war.